(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In school-age children, the presence of concomitant diseases made it difficult to diagnose AD in a timely manner: we found that children with perinatal damage to the central nervous system and intestinal dysbiosis were diagnosed more recently. Frequent exacerbations of the disease contributed to the earlier and timely diagnosis of AD.